2018
DOI: 10.1002/ece3.4451
|View full text |Cite
|
Sign up to set email alerts
|

Transmission pathways and spillover of an erythrocytic bacterial pathogen from domestic cats to wild felids

Abstract: Many pathogens infect multiple hosts, and spillover from domestic to wild species poses a significant risk of spread of diseases that threaten wildlife and humans. Documentation of cross‐species transmission, and unraveling the mechanisms that drive it, remains a challenge. Focusing on co‐occurring domestic and wild felids, we evaluate possible transmission mechanisms and evidence of spillover of “Candidatus Mycoplasma haemominutum” (CMhm), an erythrocytic bacterial parasite of cats. We examine transmission an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 70 publications
0
22
0
1
Order By: Relevance
“…NtSTs from sampled guignas and domestic cats from Chile were positioned within clades shared by domestic cats and wild felid and carnivore host species from around the world, suggesting a worldwide distribution of hemoplasmas and no phylogeographic differentiation among continents within each species-specific clade. Worldwide interspecific transmission of these pathogens between wild and domestic carnivore host species has been described by other authors 23,25,27 .…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…NtSTs from sampled guignas and domestic cats from Chile were positioned within clades shared by domestic cats and wild felid and carnivore host species from around the world, suggesting a worldwide distribution of hemoplasmas and no phylogeographic differentiation among continents within each species-specific clade. Worldwide interspecific transmission of these pathogens between wild and domestic carnivore host species has been described by other authors 23,25,27 .…”
Section: Discussionmentioning
confidence: 78%
“…These results suggest that cross-species transmission events between both hosts may occur for some hemoplasma species but are most-likely relatively rare. As other authors have suggested 23,27 , domestic cats may be the source of the global distribution of multiple strains of hemoplasmas in wild felids, and these may persist through onward transmission following spillover. Overall, we found evidence for higher levels of intraspecific, versus interspecific, transmission in both guignas and domestic cats.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Predation as a pathway of pathogen spillover from domestic cats to wild felids has been documented in various cases (e.g. Kellner et al 2018 ), and would fit within the emerging paradigm of trophic pathways leading to infections from Hepatozoon species (e.g. Maia et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%